Well Known and Unknown Henryk Sienkiewicz’s Relations with Lithuania - Fedorovič, Irena (Slavistica Vilnensis, 2021)
Henryk Sienkiewicz (1864–1916), one of the most notable novelist of Positivism epoch, the first Polish laureate of the Nobel Prize (1905), is associated with Lithuania. One of the proof to certificate this connection is his nickname „Litwos”. Another evidence is the fact of his marriage with „Lithuanian girl” Maria Szetkiewicz from Hanuszyszki (Trakai district). Not only literature researches, but also readers can remember the image of “Lauda”, so reliably represented by Sienkiewicz in his novels “Potop” (the Flood) or “Dzwonnik” (the Bellringer). Julian Krzyzanowski in the ‘50s of 20th century, in his work Henryk Sienkiewicz. Kalendarz życia i twórczości (Henryk Sienkiewicz. The callendar of his life and his output”) wrote about Sienkiewicz, and his relations with Lithuania. Only later, in ’90 of 20th c., were published other works about this author, for example, Związki Sienkiewicza z Wilnem i Wileńszczyzną (1994) (Sienkiewicz connections with Vilnius, and Vilnius region) by Maria Bokszczanin, and Sienkiewicz (1999) by Tadeusz Żabski. Famous Polish writer and also Nobel Prize winner Czeslaw Miłosz mentioned Sienkiewicz in his poetic papers and esseys. Unfortunatelly this theme was not discussed propely, and only after 100 years of novelist death, in 21st century, some facts were discovered. The latest studies by Tadeusz Bujnicki and Andrzej Rataj give a chance to rediscover and expose some new details, and once again show Sienkiewicz relations with Lithuania.